Afterword - Cynthia Enloe (Kvinder, Køn & Forskning, 2018)
Afterword to the chapter Globalization and Militarism: Feminists Make the Link, 2nd ed., p. 77-98. The afterword is written exclusively for this issue of Women, Gender & Research.